The Measurement of Cognitive Ability in Wave 12 of the HILDA Survey - Wooden, M; Wooden, Mark (My University, 2013)
In a previous paper, Wooden et al. (2012) describe the identification, development and testing of suitable measures of cognitive ability for inclusion in wave 12 of the HILDA Survey. As reported on there, three measures were proposed for inclusion. That recommendation was subsequently approved by what was then the Australian Government Department of Families, Housing, Community Services and Indigenous Affairs (now Department of Social Services). In this paper the data on cognitive ability collected in wave 12 are examined. Specifically, I: analyse willingness to participate (as reflected in item response); examine the evidence on the performance of the measures and the extent to which scores were influenced by external circumstances, interview mode, and interviewers; report summary descriptive data; and present cursory evidence on the extent to which the measures are predictive of outcomes, and more specifically the hourly wage among working-age employees. The paper concludes with a summary of issues that researchers should be aware of when using these data.
HILDA Discussion Paper Series
Keywords: Surveys and Survey Methodology -- Questionnaire development; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Questionnaire development; Surveys and Survey Methodology